2004
DOI: 10.1590/s0100-879x2004001100018
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological rehabilitation of memory deficits and activities of daily living in patients with Alzheimer's disease: a pilot study

Abstract: Patients with Alzheimer's disease (AD) gradually lose their cognitive competence, particularly memory, and the ability to perform daily life tasks. Neuropsychological rehabilitation is used to improve cognitive functions by facilitating memory performance through the use of external aids and internal strategies. The effect of neuropsychological rehabilitation through memory training -motor movements, verbal association, and categorization -and activities of daily living (ADL) training was tested in a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 18 publications
5
46
0
11
Order By: Relevance
“…Experimental studies with groups of patients with dementia have shown that non-pharmacological interventions can have a positive influence on affective variables and neuropsychiatric disorders, and this has a direct reflection on the quality of life of these patients [31][32][33][34][35] . The analysis of the ES showed that the exercise program may have positive effects for this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies with groups of patients with dementia have shown that non-pharmacological interventions can have a positive influence on affective variables and neuropsychiatric disorders, and this has a direct reflection on the quality of life of these patients [31][32][33][34][35] . The analysis of the ES showed that the exercise program may have positive effects for this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies analyzed by Heyn, Abreu and Ottenbacher 16 in another meta-analysis did not support conclusions about the benefits of regular exercise for cognition and behavior in demented patients. A possible explanation for this could be attributed to the assessment scales, which may not have been sensitive enough to reflect these benefits [31][32][33]35 .…”
Section: Discussionmentioning
confidence: 99%
“…É interessante notar que o sinal de colina é constituído de metabóli-tos da fosfatidilcolina (principal substrato da PLA 2 ), especialmente glicerofosfocolina, fosfocolina e colina livre 85 . Treinamento cognitivo também tem sido realizado clinicamente e tem sido eficaz na melhora da função de memória em sujeitos idosos com comprometimento cognitivo leve [33][34][35] e DA inicial [36][37][38] .…”
Section: Possível Participação Da Fosfolipase a 2 Na Neurogênese Promunclassified
“…Em vista dessa hipótese, os principais objetivos deste trabalho foram revisar a literatura sobre a ocorrência de neurogênese endógena no cérebro de sujeitos com DA e modelos animais de DA, bem como os efeitos de atividade cognitiva sobre a neurogênese em animais experimentais. Esse segundo objetivo se baseia em estudos mostrando que treinamento cognitivo tem sido realizado clinicamente e tem sido eficaz na melhora da função de memória em sujeitos idosos com comprometimento cognitivo leve [33][34][35] e DA inicial [36][37][38] . Com base em estudos recentes de nosso laboratório mostrando que treinamento de memória aumenta a atividade da enzima fosfolipase A 2 (PLA 2 ) em animais experimentais 39,40 e sujeitos idosos sadios 41 , um terceiro objetivo deste trabalho foi revisar a literatura sobre a relação entre a PLA 2 e a neurogênese.…”
Section: Introductionunclassified
“…Os auxílios mnemônicos externos ( c a l e n d á r i o s , diários, cadernos de memória) são estratégias da reabilitação que necessitam de estudos bem cont rolados em DA, havendo evidências que pare c e m apontar na melhora do funcionamento dos pacientes 90,94 . Dois trabalhos publicados recentemente no Brasil demonstraram efeitos positivos da re a b i l itação, tendendo à relativa estabilização da prog ressão da DA, em pacientes em uso de anticolinesterásicos 95,96 .…”
Section: Recomendações/sugestõesunclassified